(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Potassium sodium niobate (KNN) has always been one of the most potential candidates to replace lead-based piezoelectric ceramics due to its strong piezoelectric properties and environmentally friendly composition. A strong piezoelectric property is constantly influenced by the sample's densification as well as its microstructural characteristics. One of the current main issues with this KNN lead-free piezoelectric material is the difficulty in creating high-density samples by conventional preparation and sintering. Thus, KNN lead-free ceramics were synthesised using an improved solid-state method by introducing the double calcination-milling route to this process. The outcome demonstrates that, despite the presence of additional KNN secondary phases, the double calcination-milling approach contributed to the early creation of the KNN phase. When sintered pellets are subjected to a double calcination milling process, the XRD pattern revealed that the main peaks of the sample are indexed to orthorhombic K0.5Na0.5NbO3. The double calcination KNN pellet have a relative density of 90% densification which is slightly higher than that of single calcination KNN pellet which shows 88% densification.